2021
DOI: 10.1093/gji/ggab189
|View full text |Cite
|
Sign up to set email alerts
|

Local earthquake tomography of the source region of the 2018 Lombok earthquake sequence, Indonesia

Abstract: Summary We develop and present a three-dimensional (3D) seismic velocity model of the source region of the 2018 Lombok, Indonesia earthquakes by employing local earthquake tomography. The data consist of 28,728 P- and 20,713 S-wave arrival times from 3,259 events which were recorded by 20 local seismic stations. The results show that most of the significant earthquakes occur to the edge of high-velocity regions. We interpret these to represent coherent blocks of the Flores Oceanic Crust underthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Sasmi et al (2020) explained that the 2018 Lombok earthquake aftershocks were mostly distributed to the depth of < 20 km with an average hypocenter slope of ~30 o and thought to be related with the rupture zone of 2018 Lombok earthquake. These significant events of earthquake were suspected as a result of the oceanic crust slabbed to the north of Lombok Islands and caused fault segmentation (Sasmi et al, 2020;Afif et al, 2021;Priyono et al, 2021;Wang et al, 2020;Salman et al, 2020;Yang et al, 2020;Lythgoe et al, 2021). The results from these studies confirm that the lack of correlation between event depths and δt suggests the shallow anisotropic fabrics may control the main possible sources of anisotropy in this area.…”
Section: The Influence Of Structure Induced Anisotropymentioning
confidence: 59%
See 2 more Smart Citations
“…Sasmi et al (2020) explained that the 2018 Lombok earthquake aftershocks were mostly distributed to the depth of < 20 km with an average hypocenter slope of ~30 o and thought to be related with the rupture zone of 2018 Lombok earthquake. These significant events of earthquake were suspected as a result of the oceanic crust slabbed to the north of Lombok Islands and caused fault segmentation (Sasmi et al, 2020;Afif et al, 2021;Priyono et al, 2021;Wang et al, 2020;Salman et al, 2020;Yang et al, 2020;Lythgoe et al, 2021). The results from these studies confirm that the lack of correlation between event depths and δt suggests the shallow anisotropic fabrics may control the main possible sources of anisotropy in this area.…”
Section: The Influence Of Structure Induced Anisotropymentioning
confidence: 59%
“…This may be related to the influence of the crack zone formed during the 2018 Lombok significant earthquake (Sasmi et al, 2020;Afif et al, 2021;Priyono et al, 2021;Wang et al, 2020;Salman et al, 2020). Sasmi et al (2020) explained that the 2018 Lombok earthquake aftershocks were mostly distributed to the depth of < 20 km with an average hypocenter slope of ~30 o and thought to be related with the rupture zone of 2018 Lombok earthquake.…”
Section: The Influence Of Structure Induced Anisotropymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the difference is in the structure's location, which is in Lombok's northern region (Widyarta et al, 2020). Another tomographic study by Afif et al (2021) and Priyono et al (2021) found that aftershocks formed an east-west cluster due to the low seismic velocities of the local medium. High temperature, fluid, and numerous fractures are indicated by this.…”
Section: Resultsmentioning
confidence: 99%
“…One method to obtain information on subsurface structures uses seismic tomography, which requires precise earthquake hypocenters. Previous studies were related to evaluating the seismicity, structure, and subduction dynamics beneath the study area, such as local tomography inversion [3,5], Double-difference relocation method [3], and GPS observation [6]. This study used the non-linear method from Lomax to determine hypocenters around Bali and Nusa Tenggara.…”
Section: Introductionmentioning
confidence: 99%